The Influence Of Leadership Style And Competencies On Employee Motivation - Fatonah, Feti; Nalendro, Muh; Putu K, Dewa; Rizki, Muh; Abrar, Raihan (Cipta Kind Publisher, 2024)
Effective leadership and the competency of a leader have a substantialimpact on the work motivation of individual employees. Leadership elementsalso act as a yardstick for a company's success by inspiring employees to attainpeak performance. This research constitutes a review of literature focusing on theeffects of leadership and competency on employee work motivation. Theobjective of this study is to explore the influence of leadership and competencyon work motivation. The findings of this research suggest that adept leadershipand competent attributes can stimulate employee performance towardsaccomplishing the company's objectives